Naga ed-Dêr in the First Intermediate Period - Brovarski, Edward (Lockwood Press, 2018)
Beginning in 1901, George A. Reisner conducted a number of excavating campaigns in the neighbourhood of the modern village of Naga ed-Der in Upper Egypt, opposite the ancient city of Thinis, at first for the Hearst Expedition of the University of California (up to 1905) and thereafter for the Harvard University-Boston Museum of Fine Arts Expedition.0Naga ed-Der is important because of a series of ancient cemeteries extending in time from the Predynastic period to the Middle Kingdom. These cemeteries run for about six kilometres from Sheikh Farag on the north to Mesheikh on the south and form parts of a single large cemetery of the Thinite nome UE 8. In the course of the excavations at Naga ed-Der, Reisner discovered in addition extensive remains of the First Intermediate period-decorated tombs, steles, and inscribed coffins-belonging to the period extending from the end of the Sixth to the Eleventh Dynasties. The Predynastic, Early Dynastic, and Old Kingdom material from Naga ed-Der has been studied and published by Reisner and Arthur C. Mace and by Albert M. Lythgoe and Dows Dunham. Dows Dunham published seventy-five steles from Reisner's excavations in 1937.0This volume endeavours to date the material found by Reisner, including the inscribed stones published by Dunham, with a view to elucidating the history of the site in the period between the Old and Middle Kingdoms. Furthermore, a number of steles seen on the art market or in museums or private collections which, by their style, belong clearly to Naga ed-Der, have been added as supplementary material.